Cost-effectiveness of HIV prevention for high-risk groups at scale: an economic evaluation of the Avahan programme in south India - Dr. Anna Vassall, PhD; Michael Pickles, PhD; Sudhashree Chandrashekar, MBBS; Marie-Claude Boily, PhD; Govindraj Shetty, BCom; Lorna Guinness, PhD; Catherine M Lowndes, PhD; Janet Bradley, MA; Prof. Stephen Moses, MD; Prof. Michel Alary, MD; Prof. Peter Vickerman, DPhil (Elsevier, 2014)
Background: Avahan is a large-scale, HIV preventive intervention, targeting high-risk populations in south India. We assessed the cost-effectiveness of Avahan to inform global and national funding institutions who are considering investing in worldwide HIV prevention in concentrated epidemics. Methods: We estimated cost effectiveness from a programme perspective in 22 districts in four high-prevalence states. We used the UNAIDS Costing Guidelines for HIV Prevention Strategies as the basis for our costing method, and calculated effect estimates using a dynamic transmission model of HIV and sexually transmitted disease transmission that was parameterised and fitted to locally observed behavioural and prevalence trends. We calculated incremental cost-effective ratios (ICERs), comparing the incremental cost of Avahan per disability-adjusted life-year (DALY) averted versus a no-Avahan counterfactual scenario. We also estimated incremental cost per HIV infection averted and incremental cost per person reached. Findings: Avahan reached roughly 150 000 high-risk individuals between 2004 and 2008 in the 22 districts studied, at a mean cost per person reached of US$327 during the 4 years. This reach resulted in an estimated 61 000 HIV infections averted, with roughly 11 000 HIV infections averted in the general population, at a mean incremental cost per HIV infection averted of $785 (SD 166). We estimate that roughly 1 million DALYs were averted across the 22 districts, at a mean incremental cost per DALY averted of $46 (SD 10). Future antiretroviral treatment (ART) cost savings during the lifetime of the cohort exposed to HIV prevention were estimated to be more than $77 million (compared with the slightly more than $50 million spent on Avahan in the 22 districts during the 4 years of the study). Interpretation: This study provides evidence that the investment in targeted HIV prevention programmes in south India has been cost effective, and is likely to be cost saving if a commitment is made to provide ART to all that can benefit from it. Policy makers should consider funding and sustaining large-scale targeted HIV prevention programmes in India and beyond. Funding: Bill & Melinda Gates Foundation.